Effect of Bone Mineral Density on Functional and Radiological Results in Conservatively Treated Distal Radius Fractures - (:unkn) unknown (GALENOS YAYINCILIK, 2015)
Objective: This study was designed to evaluate the effect of bone mineral density on functional and radiographic results of distal radius fractures, which were treated with closed reduction and casting. Materials and Methods: Fifty-two patients [21 males, 31 females, 31 right, 21 left-wrist mean age: 63.4 years (range, 50-84)] who were treated with closed reduction and short arm casting due to fracture of distal radius were included in this study. Patients were divided into groups according to bone mineral density (BMD) measurement results as low (group 1, n=31) and normal (group 2, n=21). Groups were compared according to healing times, radiographic parameters of the last controls and Gartland-Werley functional scores. Results: The fracture type, dominant side, gender distribution and mean age were homogeneous in both group (p=0.18; p=0.96, p=0.38 and p=0.42). There were no significant differences in terms of loss of radial inclination (p=0.17), the volar tilt loss (p=0.24) and the amount of radial shortening (p=0.14) between two groups. There was also no significant difference between the groups in terms of time to union (p=0.87). Functional scores were significantly lower in group with low BMD (p=0.03) and a significant positive correlation was found between BMD and functional results (r=0.29, p=0.04). There was no significant correlation between functional scores and amount of shortening, loss of radial inclination and volar tilt (p=0.53, p=0.38 and p=0.57). Conclusion: This study showed that, lower BMD scores have no significant effect on healing time and loss of reduction of conservatively treated distal radius fractures, however affect adversely the functional results.
Keywords: Distal radius fracture; bone mineral density; conservative treatment